Government of Ethiopia's public works and complementary programmes: A mixed-methods study on pathways to reduce intimate partner violence - Ranganathan, Meghna; Pichon, Marjorie; Hidrobo, Melissa; Tambet, Heleene; Sintayehu, Wastina; Tadesse, Seifu; Buller, Ana Maria (Elsevier, 2022)
There is evidence that cash transfers reduce intimate partner violence (IPV), but less is known about the impacts of public works and complementary programmes on IPV. Using mixed-methods we examined whether and how the Ethiopian government's public works programme (that includes cash and/or food for work) alongside complementary activities that engage women and men affected IPV. We analysed midline data collected in July–October 2019 from a randomised controlled trial (RCT) designed to measure the added impacts of the complementary programming in the Amhara and Oromia regions. Eligible households for this analysis had at least one child aged 0–35 months and a primary female caregiver who was married, and under 50 years-old (n = 2604). A nested qualitative study was conducted with a sub-sample of RCT participants from February–March 2020; data included seven focus group discussions and 58 in-depth interviews. Male partners of women who reported experiencing IPV were purposively sampled. Ordinary Least Squares regression analyses were used to estimate the average treatment effect of the complementary programming, and sub-analyses were conducted on the poorest ten households from each village who received additional livelihood transfers. Qualitative data were analysed using thematic content analysis. We found no impacts of the complementary programming on IPV in the full sample, but some impacts among the poorest sample. Evidence on pathways found that both the public works and complementary programming decreased poverty-related stress and arguments within relationships and increased emotional wellbeing. There were some impacts on women's empowerment from the complementary programming. However, men's reactions to women's empowerment were mixed. There was strong evidence that engaging men in nutrition behaviour change communication contributed to improving gender relations. Our findings indicate that social protection and complementary programmes have the potential to be gender transformative and prevent the drivers of IPV.